A Training In Making Animation Video Learning Media Based On Animakers For Teachers At Mi Miftakhul Ulum Sidowungu Gresik - Nurul Agustin; Ainul Fithriyah; Rahmat Rudianto (PUDAK: Local Wisdom Community Journal, 2023)
Training on making animated videos using the Animaker application. This activity is to provide insight into making learning media videos for MI Miftakhul Ulum Sidowungu Menganti Gresik teachers with a total of 20 teachers participating. This training aims to enable teachers to develop teaching materials using a variety of media, facilitating the teaching and learning process so that students easily receive material from the teacher. Direct practical training in one of these classrooms produces animated video works using the Animaker application. The results from respondents participating in the animation video making training activity showed that on average they got a score of 90%, strongly agree and from the activity criteria of the training participants making animation videos using the Animaker application, they got a score of 90.80%. From the results of respondents and the results of participant activities, this training is very useful in increasing insight and improving teachers' abilities in using the Animaker application. By creating animated video media, students can be enthusiastic about participating in learning and studying